Desigualdade de renda e emissões de dióxido de carbono na América Latina - Mittmann, Zenir (2018)
In this paper, we investigate the role of income inequality in per capita carbon dioxide (CO2) emissions in Latin America. Recent works have explored the ambiguous theoretical links that explain the phenomenon. However, few studies investigate this issue in developing countries, and we do not find any focusing on Latin America. Our results show that, in the region, income inequality influences CO2 emissions, but the direction of the effect depends on the average income level. We demonstrate that at low and high per capita GDP levels, inequality increases emissions. In countries with middle per capita GDP, range where most of the countries in the region are found, income inequality decreases per capita CO2 emissions.